Análisis a los estados financieros de la empresa comercial “Baldosas Rocafuerte” de la ciudad de Loja, período 2020-2021. - Lozano Armijos, Victoria Sofia (2023)
The curricular integration work called: Analysis of the financial statements of the commercial company “BALDOSAS ROCAFUERTE” of the city of LOJA, period 2020-2021, has the purpose of reporting on the financial situation of the company through a financial analysis and in this way to know the economic and financial situation, so that the owner can make the right decision for his benefit. In order to meet the stated objectives, a prior visit to the company was carried out in order to obtain general and specific information about it, as well as obtaining the Financial Statements to carry out the corresponding analysis. With the information, the vertical analysis was carried out where the level of importance of each one of the accounts will be prolonged, in this way the financial and economic structure will be extended, in the same way the horizontal analysis was carried out where the increase or decrease will be prolonged. of the figures that the accounts of one period had in relation to another as a result of the operations carried out in order to determine the reasons for said alterations and to be able to carry out corrective measures and make the right decisions. The vertical and horizontal analysis allowed to know the economic structure and the variation of the different accounts that make up the economic and financial structure of the company, and it was obtained that with greater relevance are the current assets represented with 77.94% and 81, 28% with a value of $284,885.45 and $331,562.87 dollars respectively, due to the fact that its commercial activity is concentrating its values in the merchandise inventory. On the other hand, the bank account reflected a significant decrease of 54.23%, this is due to the fact that in the month of December the company cancels all the invoices of the accounts payable that it has pending. Regarding the company's liabilities, in 2020 the participation of current liabilities was 22.09% and in 2021 it was 27.94%, due to the high value of accounts payable from suppliers since the company acquired a greater number of merchandises on credit in the year 2021. Within the economic structure, operational expenses have the highest incidence, in 2020 it represents 101.84% and 93.53% in the following period, such values, being very high, affect the company's profits. Next, financial indicators were applied, through these it was determined that the company has an adequate level of liquidity to cover the acquired debts, inventory rotation is limited since they are carried out every two or three times a year, the average days of collection are adequate since the company complies with the payment to its suppliers in the short term, providing confidence, the same that benefits the company. 5 Finally, a financial analysis report was made that contains a summary of the results obtained, conclusions and recommendations about the economic and financial situation of the commercial company "Baldosas Rocafuerte" in order to provide a guide for adequate decision making. aimed at improving the management of economic activities that ensure the stability of the company.